Sequences and series (3)

Calculus Level 5

i = 0 j = 0 k = 0 1 3 i 3 j 3 k , i j k \large \sum_{i=0}^{\infty} \sum_{j=0}^{\infty} \sum_{k=0}^{\infty} \dfrac{1}{3^i \ 3^j \ 3^k}, \quad i≠j≠k

Find the value of the above triple summation. If your answer comes in form of a b \dfrac{a}{b} where a a and b b are positive coprime integers, then enter a + b a+b as your answer.

Note: i i , j j , and k k are distinct.


Inspiration .


For more problems try my new set


The answer is 289.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tapas Mazumdar
May 5, 2017

We break down the sum into three separate sums as follows

S = i = 0 j = 0 k = 0 1 3 i 3 j 3 k ( i j k ) = i = 0 1 3 i S 1 S 1 = j = 0 , j i 1 3 j S 2 S 2 = k = 0 , k i , k j 1 3 k \begin{aligned} \displaystyle \bullet & \ S = \sum_{i=0}^{\infty} \sum_{j=0}^{\infty} \sum_{k=0}^{\infty} \dfrac{1}{3^i 3^j 3^k} (i \neq j \neq k) = \sum_{i=0}^{\infty} \dfrac{1}{3^i} \cdot S_1 \\ \displaystyle \bullet & \ S_1 = \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{3^j} \cdot S_2 \\ \displaystyle \bullet & \ S_2 = \sum_{k=0, \ k \neq i, \ k \neq j}^{\infty} \dfrac{1}{3^k} \end{aligned}

Starting with S 2 S_2

S 2 = k = 0 , k i , k j 1 3 k = k = 0 1 3 k 1 3 i 1 3 j = 3 2 1 3 i 1 3 j \begin{aligned} \displaystyle S_2 &= \sum_{k=0, \ k \neq i, \ k \neq j}^{\infty} \dfrac{1}{3^k} \\ \displaystyle &= \sum_{k=0}^{\infty} \dfrac{1}{3^k} - \dfrac{1}{3^i} - \dfrac{1}{3^j} \\ \displaystyle &= \dfrac 32 - \dfrac{1}{3^i} - \dfrac{1}{3^j} \end{aligned}

Now

S 1 = j = 0 , j i 1 3 j S 2 = j = 0 , j i 1 3 j ( 3 2 1 3 i 1 3 j ) = ( 3 2 1 3 i ) j = 0 , j i 1 3 j j = 0 , j i 1 9 j = ( 3 2 1 3 i ) 2 ( 9 8 1 9 i ) = 9 8 3 1 3 i + 2 1 9 i \begin{aligned} \displaystyle S_1 &= \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{3^j} \cdot S_2 \\ \displaystyle &= \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{3^j} \left( \dfrac 32 - \dfrac{1}{3^i} - \dfrac{1}{3^j} \right) \\ \displaystyle &= \left( \dfrac 32 - \dfrac{1}{3^i} \right) \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{3^j} - \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{9^j} \\ \displaystyle &= {\left( \dfrac 32 - \dfrac{1}{3^i} \right)}^2 - \left( \dfrac 98 - \dfrac{1}{9^i} \right) \\ \displaystyle &= \dfrac 98 - 3 \cdot \dfrac{1}{3^i} + 2 \cdot \dfrac{1}{9^i} \end{aligned}

Hence

S = i = 0 1 3 i S 1 = i = 0 1 3 i ( 9 8 3 1 3 i + 2 1 9 i ) = 9 8 i = 0 1 3 i 3 i = 0 1 9 i + 2 i = 0 1 27 i = 9 8 × 3 2 3 × 9 8 + 2 × 27 26 = 81 208 \begin{aligned} \displaystyle S &= \sum_{i=0}^{\infty} \dfrac{1}{3^i} \cdot S_1 \\ \displaystyle &= \sum_{i=0}^{\infty} \dfrac{1}{3^i} \left( \dfrac 98 - 3 \cdot \dfrac{1}{3^i} + 2 \cdot \dfrac{1}{9^i} \right) \\ \displaystyle &= \dfrac 98 \sum_{i=0}^{\infty} \dfrac{1}{3^i} - 3 \sum_{i=0}^{\infty} \dfrac{1}{9^i} + 2 \sum_{i=0}^{\infty} \dfrac{1}{{27}^i} \\ \displaystyle &= \dfrac 98 \times \dfrac 32 - 3 \times \dfrac 98 + 2 \times \dfrac{27}{26} \\ \displaystyle &= \dfrac{81}{208} \end{aligned}

Thus, a b = 81 208 a + b = 289 \dfrac ab = \dfrac{81}{208} \implies a+b = \boxed{289} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...